2015
DOI: 10.1111/fwb.12686
|View full text |Cite
|
Sign up to set email alerts
|

Riparian plant guilds of ephemeral, intermittent and perennial rivers

Abstract: 1. Plant functional types (or guilds) increasingly are being used to predict vegetation response to global changes. Continued human population growth coupled with projected warmer and drier climate will alter the hydrologic regimes of many arid-zone rivers, including intermittent rivers. We aimed to identify (i) woody plant guilds associated with distinct stream types of an arid region and (ii) plant traits indicating adaptation to the selective pressures of water availability and fluvial disturbance. 2. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 107 publications
(120 reference statements)
2
104
1
2
Order By: Relevance
“…Such invasive species and lianas (e.g., M. vitifolia and H. scandens) are considered as pioneer species because they easily adapt and colonize a disturbed habitat (Stromberg & Merritt, 2016). However, the water use pattern of two invasive plants (C. odorata and T. diversifolia) was particularly different from other species in our study.…”
Section: Proportional Contribution Of Soil Water At Different Depthmentioning
confidence: 59%
“…Such invasive species and lianas (e.g., M. vitifolia and H. scandens) are considered as pioneer species because they easily adapt and colonize a disturbed habitat (Stromberg & Merritt, 2016). However, the water use pattern of two invasive plants (C. odorata and T. diversifolia) was particularly different from other species in our study.…”
Section: Proportional Contribution Of Soil Water At Different Depthmentioning
confidence: 59%
“…The deciduous nutrient‐demanding plants stand out as being disfavoured in highly disturbed sites, as they contain species morphologically unfit to face floods. Similarly, traits related to fluvial disturbance are required to explain the riparian functional composition in Mediterranean and semi‐arid environments (Kyle & Leishman, ; Stromberg & Merritt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Trait‐based frameworks have been encouraged to provide a more general understanding of the adaptive strategies of riparian plants to the fluvial setting of rivers (Aguiar, Orestes Cerdeira, Martins, & Ferreira, ; Lawson, Fryirs, Lenz, & Leishman, ; Stromberg & Merritt, ), or to disturbance (Stahl et al., ), especially when shifts in species diversity following environmental changes are only rudimentarily understood (Kominoski et al., ). Several studies have reported clear relationships between riparian trait composition (rooting habit, seed mass and wood density) and water availability.…”
Section: Introductionmentioning
confidence: 99%